Oral hygiene behavior, smoking, and perceived oral health problems among university students - Shah, Altaf Hussain (J Int Soc Prev Community Dent, 2015)
BACKGROUND: Behavioral aspects play a major role in the prevention of oral diseases. Moreover, not many people are aware of the relationship of smoking with potential oral diseases. Therefore, the aims of this study were to analyze oral hygiene behavior, smoking habits, and perceived oral health problems among a sample of university students in Al-Kharj, Saudi Arabia. MATERIALS AND METHODS: A self-administered questionnaire about oral hygiene behavior, smoking, and perceived oral health problems was developed. The questionnaires were mainly distributed in Medical, Dental, and Pharmacy colleges of the university. Questionnaires completed at other colleges were included under the term “other colleges.” RESULTS: Overall, 380 questionnaires were returned. Majority of the students (92.4%) reported cleaning their teeth. Most of the students reported cleaning teeth once daily (48.7%). Just over a half (55.8%) reported having a dental check-up in the last 6 months, and a significantly higher number of dental students reported having a dental check-up (P < 0.05). Regarding smoking, the majority (63.4%) reported to have never smoked while 17.3% reported that they were smoking frequently. About 17.6% perceived oral health problems, including a significant proportion of those who reported frequent smoking. CONCLUSIONS: Oral hygiene behavior exhibited by the university students sample was similar. Majority cleaned their teeth, although only once. Smoking habit was not exhibited by the vast majority of students. Frequent smokers perceived oral health problems more than other students.